A novel covert channel based on the IP header record route option. (10th August 2007) - Trabelsi, Zouheir; El-Sayed, Hesham; Frikha, Lilia; Rabie, Tamer
In this paper we propose a novel covert channel for exchanging secret information, based on the IP header record route options. Instead of encrypting a secret message or embedding it into a multimedia object, as in traditional steganography, we process the entire message and generate several IP packets with different types to carry the secret information. Thereby we foil an eavesdropper who is primarily applying statistical tests to detect encrypted channels. We show that our approach provides more protection against steganalysis and sniffing attacks, and gives a covert channel capacity which is an order of magnitude higher than traditional methods.